Exploiting ionisable nature of PEtOx-co-PEI to prepare pH sensitive, doxorubicin-loaded micelles. (2nd October 2020) - Ozturk, Naile; Kara, Asli; Gulyuz, Sevgi; Ozkose, Umut Ugur; Tasdelen, Mehmet Atilla; Bozkir, Asuman; Yilmaz, Ozgur; Vural, Imran
Abstract: Aims: This study was conducted to evaluate block copolymers containing two different poly(ethyleneimine) (PEI) amounts, as new pH-sensitive micellar delivery systems for doxorubicin. Methods: Micelles were prepared with block copolymers consisting of poly(2-ethyl-2-oxazoline)- co -poly(ethyleneimine) (PEtOx- co -PEI) and poly(ε-caprolactone) (PCL) as hydrophilic and hydrophobic blocks, respectively. Doxorubicin loading, micelle size, pH-dependent drug release, and in vitro cytotoxicity on MCF-7 cells were investigated. Results: The average size of drug-loaded micelles was under 100 nm and drug loading was between 10.7% and 48.3% (w/w). pH-sensitive drug release was more pronounced (84.7% and 68.9% (w/w) of drug was released at pH 5.0 and pH 7.4, respectively) for the micelles of the copolymer with the lowest PEI amount. The cell viability of doxorubicin-loaded micelles which were prepared by the copolymer with the lowest PEI amount was 28–33% at 72 h. Conclusions: PEtOx- co -PEI- b -PCL micelles of this copolymer were found to be stable and effective pH-sensitive nano-sized carriers for doxorubicin delivery.